Evaluation of Onion (Allium cepa L.) Genotypes for Tolerance to Thrips (Thrips tabaci L.) and Purple Blotch [Alternaria porri (Ellis) Ciferri] - Tripathy, P.; Priyadarshini, A.; Das, S. K.; Sahoo, B. B.; Dash, D. K. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted in onion to identify the advanced lines or varieties tolerant to onion thrips and/or purple blotch disease with high yield potential. Twenty one varieties and advanced lines along with five national checks were evaluated during rabi, 2009-10 against onion thrips and purple blotch disease at Sambalpur, Odisha, India under AINRP on Onion and Garlic by adopting RBD with three replications. The data on thrips infestation were transformed and subjected to statistical analysis. The results indicated that NRCRO-3, NRCWO-3, NRCWO-4 and VG-19 showed tolerance to both thrips (25.91 to 28.28 thrips plant-1) as well as purple blotch (PDI of 42.83 to 51.66%). The cultivars, Bhima Super, NRCWO-3, NRCRO-4 and the control, Arka Niketan produced significantly high total bulb yield (325.41 to 376.00 q ha-1) having better tolerance to thrips (25.91 to 32.42 thrips plant-1) and Purple Blotch (42.83 to 56.50%). The cultivar with high yield potential having tolerance to both onion thrips and purple blotch disease identified for Odisha condition are Bhima Super, NRCRO-4, NRCWO-3 of DOGR, Pune and Arka Niketan of IIHR, Bangalore.